2001
DOI: 10.1083/jcb.200105060
|View full text |Cite
|
Sign up to set email alerts
|

The bHLH transcription factor Mist1 is required to maintain exocrine pancreas cell organization and acinar cell identity

Abstract: The pancreas is a complex organ that consists of separate endocrine and exocrine cell compartments. Although great strides have been made in identifying regulatory factors responsible for endocrine pancreas formation, the molecular regulatory circuits that control exocrine pancreas properties are just beginning to be elucidated. In an effort to identify genes involved in exocrine pancreas function, we have examined Mist1, a basic helix-loop-helix transcription factor expressed in pancreatic acinar cells. Mist1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
298
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 252 publications
(320 citation statements)
references
References 49 publications
17
298
0
1
Order By: Relevance
“…59 However, b-catenin expression was found to be decreased in the acini (Figure 9a), similar to that seen with mist1 mutants. 82 The general reduction in b-catenin expression is supported by Western blot analysis, which showed that there was an overall decrease in total b-catenin levels in the pancreas (Figure 9b). This decrease in b-catenin was evident in both 3-and 7-day-old mutant samples and thus occurred prior to the onset of the severe acinar cell apoptosis.…”
Section: Tg737 Orpk Pancreatic Phenotype Is Associated With Alteratiomentioning
confidence: 67%
See 1 more Smart Citation
“…59 However, b-catenin expression was found to be decreased in the acini (Figure 9a), similar to that seen with mist1 mutants. 82 The general reduction in b-catenin expression is supported by Western blot analysis, which showed that there was an overall decrease in total b-catenin levels in the pancreas (Figure 9b). This decrease in b-catenin was evident in both 3-and 7-day-old mutant samples and thus occurred prior to the onset of the severe acinar cell apoptosis.…”
Section: Tg737 Orpk Pancreatic Phenotype Is Associated With Alteratiomentioning
confidence: 67%
“…80,81 In addition, the exocrine pancreas disorganization and apoptosis observed in mice lacking mist1, a basic helix-loophelix transcription factor expressed in the acinar cells, is associated with defects in the adherens junctions and loss of catenin proteins. 82 To explore the possibility that the pathology in Tg737 orpk mutants might also affect the adherens junctions, we analyzed the expression and localization of b-catenin by immunofluorescence and by Western blot analysis.…”
Section: Tg737 Orpk Pancreatic Phenotype Is Associated With Alteratiomentioning
confidence: 99%
“…Because MIST1 is restricted to professional secretory cells (e.g., acinar cells), we asked if nonsecretory cells could similarly induce Mist1 expression upon ER stress. For these studies, we utilized a number of human pancreatic ductal cell lines that normally do not express Mist1 (14,20,25,40,41). In all cases, treatment of cells with thapsigargin led to induction of Xbp1s and Mist1 transcripts ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the basic helix-loop-helix (bHLH) transcription factor MIST1 (encoded by Bhlha15) has emerged as a potent regulator of a wide variety of secretory cell functions and responses to stress (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Secretory cells lacking MIST1 exhibit structural and functional defects, including altered cytoskeletal organization, a change in cell polarity, and improper cell-to-cell communication (12,17,(19)(20)(21). Interestingly, the most severe phenotype observed in Mist1 knockout (Mist1 KO ) cells is a nearly complete loss of secretory capacity (21,22), a tantalizing finding that hints at a much more extensive role for MIST1 and its target genes beyond mere regulation of cargo-cytoskeletal interactions.…”
mentioning
confidence: 99%
“…MIST1 is first expressed prior to differentiation of acinar cells in the pancreas [2], and directly regulates expression of the cell cycle regulator, p21 [3], which has not been linked to secretion compartment. In addition, the expression of a number of genes, such as Atp2c2, is completely lost in Mist1 À/À acinar cells [4].…”
mentioning
confidence: 99%